Ribosome profiling enhances understanding of mycobacterial translation - Sawyer, Elizabeth B.; Cortes, Teresa (Frontiers in Microbiology, 2022)
A recent addition to the -omics toolkit, ribosome profiling, enables researchers to gain insight into the process and regulation of translation by mapping fragments of mRNA protected from nuclease digestion by ribosome binding. In this review, we discuss how ribosome profiling applied to mycobacteria has led to discoveries about translational regulation. Using case studies, we show that the traditional view of ‘canonical’ translation mechanisms needs expanding to encompass features of mycobacterial translation that are more widespread than previously recognised. We also discuss the limitations of the method and potential future developments that could yield further insight into the fundamental biology of this important human pathogen.